The Study of Properties of n-D Analytic Signals and Their Spectra in Complex and Hypercomplex Domains - Snopek, Kajetana Marta (Společnost pro radioelektronické inženýrství, 2012)
In the paper, two various representations of a n-dimensional (n-D) real signal u(x1,x2,…,xn) are investigated. The first one is the n-D complex analytic signal with a single-orthant spectrum defined by Hahn in 1992 as the extension of the 1-D Gabor’s analytic signal. It is compared with two hypercomplex approaches: the known n-D Clifford analytic signal and the Cayley-Dickson analytic signal defined by the Author in 2009. The signal-domain and frequency-domain definitions of these signals are presented and compared in 2-D and 3-D. Some new relations between the spectra in 2-D and 3-D hypercomplex domains are presented. The paper is illustrated with the example of a 2-D separable Cauchy pulse.
Keywords: Analytic signals; Cayley-Dickson algebra; Clifford algebra; Clifford Fourier transform; Quaternion Fourier transform; Octonion Fourier transform